ANALISIS POTENSI LIKUEFAKSI DAERAH PALU BERDASARKAN KECEPATAN GELOMBANG GESER DAN PERCEPATAN TANAH MAKSIMUM (STUDI KASUS GEMPABUMI PALU 28 SEPTEMBER 2018 MW 7,4) - Sandy Tri Gustono; Haura Dhiya Amaninida; Arif Alhazmi Fauzi (JFT : Jurnal Fisika dan Terapannya, 2021)
The Palu-Donggala earthquake on 28th September 2018 caused huge losses, especially losses caused by liquefaction in several regions. Liquefaction is a phenomenon in which the strength of the soil layers is reduced due to earthquake shaking. So far, many studies on liquefaction have used Cone Penetration Test (CPT) and Standard Penetration Test (SPT) data, whereas shear wave velocity (VS) data can be an alternative for the research. This study aims to analyze the potential for liquefaction after the earthquake on 28th September 2018 by using shear wave velocity data (VS) and the NCEER method at three different peak ground acceleration. This study uses measurement data that has been carried out at 67 points around the Palu area, Central Sulawesi. The potential of the liquefaction is determined based on the value of the shear wave velocity (VS) which is then analyzed to obtain the Factor of Safety (FS) value which obtained from a comparison of the value of the Cyclic Resistance Ratio (CRR) and the value of the Cyclic Stress Ratio (CSR). The area is assumed to have a liquefaction potential if the FS value is less than one. Based on the results of this research, almost all the areas show the potential for liquefaction in the three values of peak ground acceleration. The only thing that distinguishes the three results is the total thickness of the liquefaction layer at each measurement point.